FSI simulation of flexible tandem insect wings in counter stroke - Chen, Ya Hui (2018)
Bionic micro-air vehicles (MAV) having the maneuverability of dragonflies would be capable of fast forward flight, hovering and even backward flight. In order to achieve desirable designs for high performing MAVs, it is essential to understand the aerodynamics and structures of the insect wings and more importantly, the interactions between the operating flows and flexible structural wings. Here, we present a fluid-structure interaction model which integrates the realistic structural flexibility of the dragonfly wings with the actual counter-stroke flapping trajectories. Hence, we are able to study the aero-elastic deformation and aerodynamic forces acting on the flapping wings, in the hope that future MAV designs would perform closer to the agile natural fliers. Verification of the simulation framework is performed by a number of rigorous tests with comparison to past experiments and simulations.